Metagenomic Insights into the Taxonomic and Functional Features of Traditional Fermented Milk Products from Russia - Alexander G. Elcheninov; Kseniya S. Zayulina; Alexandra A. Klyukina; Mariia K. Kremneva; Ilya V. Kublanov; Tatiana V. Kochetkova (Microorganisms, 2023)
Fermented milk products (FMPs) contain probiotics that are live bacteria considered to be beneficial to human health due to the production of various bioactive molecules. In this study, nine artisanal FMPs (kefir, ayran, khurunga, shubat, two cottage cheeses, bryndza, khuruud and suluguni-like cheese) from different regions of Russia were characterized using metagenomics. A metagenomic sequencing of ayran, khurunga, shubat, khuruud and suluguni-like cheese was performed for the first time. The taxonomic profiling of metagenomic reads revealed that Lactococcus species, such as Lc. lactis and Lc. cremoris prevailed in khuruud, bryndza, one sample of cottage cheese and khurunga. The latter one together with suluguni-like cheese microbiome was dominated by bacteria, affiliated to Lactobacillus helveticus (32–35%). In addition, a high proportion of sequences belonging to the genera Lactobacillus, Lactococcus and Streptococcus but not classified at the species level were found in the suluguni-like cheese. Lactobacillus delbrueckii, as well as Streptococcus thermophilus constituted the majority in another cottage cheese, kefir and ayran metagenomes. The microbiome of shubat, produced from camel’s milk, was significantly distinctive, and Lentilactobacillus kefiri, Lactobacillus kefiranofaciens and Bifidobacterium mongoliense represented the dominant components (42, 7.4 and 5.6%, respectively). In total, 78 metagenome-assembled genomes with a completeness ≥ 50.2% and a contamination ≤ 8.5% were recovered: 61 genomes were assigned to the Enterococcaceae, Lactobacillaceae and Streptococcaceae families (the Lactobacillales order within Firmicutes), 4 to Bifidobacteriaceae (the Actinobacteriota phylum) and 2 to Acetobacteraceae (the Proteobacteria phylum). A metagenomic analysis revealed numerous genes, from 161 to 1301 in different products, encoding glycoside hydrolases and glycosyltransferases predicted to participate in lactose, alpha-glucans and peptidoglycan hydrolysis as well as exopolysaccharides synthesis. A large number of secondary metabolite biosynthetic gene clusters, such as lanthipeptides, unclassified bacteriocins, nonribosomal peptides and polyketide synthases were also detected. Finally, the genes involved in the synthesis of bioactive compounds like β-lactones, terpenes and furans, nontypical for fermented milk products, were also found. The metagenomes of kefir, ayran and shubat was shown to contain either no or a very low count of antibiotic resistance genes. Altogether, our results show that traditional indigenous fermented products are a promising source of novel probiotic bacteria with beneficial properties for medical and food industries.